Modulation of the Hypothalamic Nutrient Sensing Pathways by Sex and Early-Life Stress - Ruigrok, Silvie R.; Stöberl, Nina; Yam, Kit-Yi; de Lucia, Chiara; Lucassen, Paul J.; Thuret, Sandrine; Korosi, Aniko (Frontiers in Neuroscience, 2021)
There are sex differences in metabolic disease risk, and early-life stress (ES) increases the risk to develop such diseases, potentially in a sex-specific manner. It remains to be understood, however, how sex and ES affect such metabolic vulnerability. The hypothalamus regulates food intake and energy expenditure by sensing the organism’s energy state via metabolic hormones (leptin, insulin, ghrelin) and nutrients (glucose, fatty acids). Here, we investigated if and how sex and ES alter hypothalamic nutrient sensing short and long-term. ES was induced in mice by limiting the bedding and nesting material from postnatal day (P)2-P9, and the expression of genes critical for hypothalamic nutrient sensing were studied in male and female offspring, both at P9 and in adulthood (P180). At P9, we observed a sex difference in both Ppargc1a and Lepr expression, while the latter was also increased in ES-exposed animals relative to controls. In adulthood, we found sex differences in Acacb, Agrp and Npy expression, whereas ES did not affect the expression of genes involved in hypothalamic nutrient sensing. Thus, we observe a pervasive sex difference in nutrient sensing pathways and a targeted modulation of this pathway by ES early in life. Future research is needed to address if the modulation of these pathways by sex and ES is involved in the differential vulnerability to metabolic diseases.